Analisis Perubahan Luasan Mangrove Menggunakan Citra Landsat 7 dan Landsat 8 di Teluk Jor, Kecamatan Jerowaru, Kabupaten Lombok Timur - Muh. Marwan; Himawan, Mahardika Rizqi; Amir, Sadikin (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
Mangroves are vegetation that generally have woody stems and consist of shrubs whose life cycle is on the coast and can adapt to tidal seawater. This study aims to identify mangrove species, density conditions, frequency, damage criteria, and temporal changes in mangrove areas using Landsat 7 ETM and Landsat 8 OLI-TIERS imagery data in Teluk Jor. This research was conducted from June to July 2024 in Teluk Jor with a total of 9 observation plots. The methods used in this study include remote sensing methods and location point determination using purposive sampling methods. The data analysis used in this study includes vegetation density analysis and remote sensing analysis for mangrove mapping. The results showed that there were 6 types of mangroves found in Teluk Jor, namely Avicennia marina, Ceriops tagal, Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba, and Sonnerati caseolaris. The highest density of mangrove species in Teluk Jor was Rhizophora apiculata with 3,034 ind/ha, and the lowest density of mangrove species was Ceriops tagal with 67 ind/ha, with the highest frequency being Rhizophora apiculata. The highest total mangrove vegetation density in the second transect was 3,833 ind/ha, and the lowest total mangrove vegetation density in the third transect was 1,967 ind/ha. The standard criteria for mangrove forest damage in Teluk Jor are in good condition with dense density, and there has been a decrease in the mangrove ecosystem area from 2003 to 2023 by 72.94 Ha.